Friday

March 27, 2015

March 27, 2015

Posted by **calculus** on Thursday, September 19, 2013 at 11:49am.

- calculus -
**Steve**, Thursday, September 19, 2013 at 11:53amjust use the product rule

If y = fg, then

y' = f'g + fg'

So,

dy.dx = -sinx.sinx + cosx.cosx

= cos^2x - sin^2x

= cos2x

Or, you could have noticed that

y = 1/2 sin2x, so

y' = cos2x

**Answer this Question**

**Related Questions**

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Calculus - If y=3/(sinx+cosx) , find dy/dx A. 3sinx-3cosx B. 3/(sinx+cosx)^2 C...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Calculus 2 Trigonometric Substitution - I'm working this problem: ∫ [1-tan...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...